Alkyl Substitution Effect on Oxidation Stability of Sulfone‐Based Electrolytes. Issue 5 (16th February 2016) - Su, Chi‐Cheung; He, Meinan; Redfern, Paul; Curtiss, Larry A.; Liao, Chen; Zhang, Lu; Burrell, Anthony K.; Zhang, Zhengcheng
Abstract: Organic sulfone compounds have been widely used as high‐voltage electrolytes for lithium‐ion batteries for decades. However, owing to the complexity of the synthesis of new sulfones, only a few commercially available sulfones have been studied. In this paper, we report the synthesis of new sulfone compounds with various substituent groups and the impact of the substituent group on the oxidation stability of sulfones. Electrochemical floating tests using a 5 V LiNi0.5 Mn1.5 O4 spinel cathode and density functional theory calculations showed that the cyclopentyl‐substituted sulfone McPS suffered from oxidation instability, starting from 4.9 V versus Li + /Li, as observed by the large leakage currents. On the other hand, the isopropyl‐substituted sulfone MiPS and tetramethylene substituted sulfone TMS showed much improved oxidation stability under identical testing conditions. The substitution structure of the sulfone plays a significant role in the determination of its oxidative stability and should first be considered for the development of new sulfone‐based electrolytes for high‐voltage, high‐energy lithium‐ion batteries. Abstract : Tactical substitutions : New sulfone compounds with various substitutions are synthesized. The cyclopentyl‐substituted sulfone McPS suffers from the oxidative decomposition at 4.9 V (vs. Li + /Li) in a LiNi0.5 Mn1.5 O4 cell, whereas the isopropyl‐ and tetramethylene‐substituted sulfones MiPS and TMS show much improved oxidation stability. Both experiment and quantum chemistry calculations confirm that the substitution structure of the sulfone dictates the oxidative stability.